2015
DOI: 10.46989/001c.20704
|View full text |Cite
|
Sign up to set email alerts
|

Molluscicidal and Piscicidal Activities of Extracts of Castor (Ricinus communis) Bean for Aquaculture Management

Abstract: As from January 2010 The Israeli Journal of Aquaculture-Bamidgeh (IJA) will be published exclusively as an on-line Open Access (OA) quarterly accessible by all AquacultureHub (http://www.aquaculturehub.org) members and registered individuals and institutions. Please visit our website (http://siamb.org.il) for free registration form, further information and instructions. This transformation from a subscription printed version to an on-line OA journal, aims at supporting the concept that scientific peer-reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…After 24 h, aqueous extracts of wild beets and oleander exhibited the most significant percentage mortality of 90 -100%, whereas Jimpson weed showed 70% mortality (Kassem et al, 1993), as well as Olofintiye et al (2011) found larvae mosquito mortality rate under 50%, but at 100% concentration, it reached 100%. Additionally, Baleta et al (2015) observed it was toxicity more pronounced in small golden apple snails than large snails. Also, the boiling water extract for the leaf of Datura stramonium has phenolic compounds that cause 57.5% repulsion for insects (Amira et al, 2020).…”
Section: Introductionmentioning
confidence: 93%
“…After 24 h, aqueous extracts of wild beets and oleander exhibited the most significant percentage mortality of 90 -100%, whereas Jimpson weed showed 70% mortality (Kassem et al, 1993), as well as Olofintiye et al (2011) found larvae mosquito mortality rate under 50%, but at 100% concentration, it reached 100%. Additionally, Baleta et al (2015) observed it was toxicity more pronounced in small golden apple snails than large snails. Also, the boiling water extract for the leaf of Datura stramonium has phenolic compounds that cause 57.5% repulsion for insects (Amira et al, 2020).…”
Section: Introductionmentioning
confidence: 93%